First report of megaselia sp. (diptera: phoridae) as a parasitoid of sphenarium purpurascens purpurascens (orthoptera: pyrgomorphidae) - Quesada-Béjar, Venecia; Nájera-Rincón, Miguel B.; Reyes-Novelo, Enrique; González-Esquivel, Carlos E. (Instituto de Ecología, A.C., 2017)
The presence of a Megaselia species parasitizing Sphenarium purpurascens purpurascens is documented for the first time. Some data on its biology are included from specimens collected in maize agroecosystems in the municipality of Erongarícuaro, Michoacan, Mexico.